A transparência como ferramenta de ampliação do caráter democrático nos Conselhos Universitários das instituições federais de ensino superior : o caso da Universidade Federal do Espírito Santo - Monteiro, Fernando Mota (2013)
The University Council of the Federal University of Espírito Santo (Ufes) is the highest deliberative body of the institution. Its composition obeys the Law 5.540/1968, which determines that 70% of its members must belong to the faculty, fact that tends to lead to disparities between the political strength of the teaching category and the category of technical and administrative educational employees, a factor that has the potential to destabilize democratically decisions issued by the Council. In order to mitigate such differences, points up the implementation of administrative transparency tools, to provide social audits and expand democratic balance of forces etween the categories, in allusion to the Jürgen Habermas/ Discourse Theory . The theory proclaims that the participation of the collective within the government produces better reasoned speeches, more debated and democratically more embracing, and argues that the deliberative participation must be performed by institutionalized means. For this theory to be applied, the access to information must be broad, to provide means for the university community to monitor the Council s everyday. By conducting documentary research, was found that the Ufes University Council/ s website obeys poorly the provisions of Law 12.527/2011, commonly named Access to Information Law , which confirms that the decision-making processes of the collegiate body remain immersed in a secrecy culture . It was also noted that the Federal University of Santa Catarina/ s (UFSC) Councyl fully complies the mentioned law, and sets up as an example of better-practices, particularly related to the available information posted on its website, which provides the live streaming of their sessions. Through interviews taken with the employees directly bounded to the Ufes and UFSC/ s University Councils, a systematic comparative analysis has been conducted, which concluded that, even with the hegemony of the faculty at both institutions, the debate level in UFSC/ s collegiate is considered more democratical, while in UFES was pointed the predominance of teaching category in the discussions, and that, at UFSC, the university community is considered interested in the issues addressed by the collegiate, while in Ufes the answer is the complete opposite. From these analyzes, has been proposed an action platform to be implemented by the Ufes/ administration, aimed at improve access to information through the website of the Superior Collegiate Bodies Administration Department, with an inclusion of live broadcast of the University Council/ s sessions and a participation tool for the university community, live also, during the discussion of some points of the Council/ s agenda. Based on the theoretical framework , on the conducted research and on the inferential analysis, it was concluded that the Ufes/ University Council sessions opening to the public, contemplating the right to speak by the university community, has the potential to expand the democratic characteristic of it s decisions, and that this potential can be quantitatively measured, retrospectively from this study/ s application, by opinion polls